2009
DOI: 10.14723/tmrsj.34.141
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Photonic Properties of Indolocarbazole Derivatives

Abstract: In this study, the syntheses of indolo[3,2-b]carbazole (INC) derivatives have been investigated, which possessed the planer and conjugated structure and showed the strong blue fluorescence by the irradiation of UV light. In order to improve the solubility of INC, N-alkylated INC derivatives were prepared by the reaction of INC with NaH followed by the addition of alkyl halides, the carbon numbers of which were C 1-C 10. The obtained alkylated INCs were soluble in some solvents, and the unique thermal propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In our previous work, we estimated the photoluminescence quantum yields of INC and alkylated INC to be 0.50 and 0.52-0.54, respectively. 30 Therefore, copolymers containing the INC moiety are candidates for photonic or electronic materials in the emission or carrier-transporting layer of electroluminescence devices.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work, we estimated the photoluminescence quantum yields of INC and alkylated INC to be 0.50 and 0.52-0.54, respectively. 30 Therefore, copolymers containing the INC moiety are candidates for photonic or electronic materials in the emission or carrier-transporting layer of electroluminescence devices.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous paper, 30 1-octyl-7-(4-vinylbenzyl)indolo[3,2-b]carbazole (5) was prepared as a monomer compound by a reaction of 1-iodooctane with the INC anion derived from the reaction of INC with sodium hydride, followed by the addition of p-chloromethylstyrene. However, the yield of monomer 5 was very low because the mono-alkylation of the Nposition of INC proceeded with a large amount of byproduct, dialkylated INC, and so on.…”
Section: Preparation Of the Inc-containing Monomermentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum absorption and photoluminescence intensity were observed at 340 nm and 421 nm, respectively. It was found that the absorption and photoluminescence spectra of CP-1, CP-2 were similar to that of N, N'-dioctyl INC [8]. Therefore, the absorption and photoluminescence behavior of these copolymer solutions seemed to be derived from the INC moiety.…”
Section: Photonic Properties Of Copolymersmentioning
confidence: 85%
“…However, only few studies have been reported on the synthesis of INC-containing polymers. In our previous study [7][8][9], we have investigated the synthesis of a novel monomer containing indolocarbazole moiety, 1-(4-vinylbenzyl)-7-octylindolo[3,2-b]carbazole (VINC-C 8 ), and the copolymers of VINC-C 8 with styrene were prepared by a radical polymerization. Then, it was found that the obtained copolymers showed the amorphous state and the thermal stability of the copolymers increased as the INC content increased.…”
Section: Introductionmentioning
confidence: 99%